Information environment for enhanced interaction and value-adding of electronic documents. - Liew, Chern Li. (2008)
The research investigates how electronic documents (e-documents) could be enhanced in the electronic environment to make these documents more valuable to end-users. This research aimed to find out how a wide range of information searching, analysis and communicating tasks involved in interacting with e-documents could be supported within a single user interface (UI) environment.